Money as an inflationary phenomenon - Markus Pasche (Friedrich Schiller University Jena, 2018)
Empirical tests of the quantity theory and particularly the neutrality of money are based on the idea that money growth "explains", to some extent, inflation. Modern macroeconomic theory, however, considers inflation targeting central banks which use the interest rate as a policy tool, while money is seen as an endogenous outcome of financial intermediation, i.e. credit creation. A simple NKM model with fiat money demonstrates that money growth is tied to inflation, changes of output and interest rate changes. The latter are determined by inflation and output gap if we consider an inflation-targeting central bank. The quantity equation emerges from the macroeconomic transmission process but the economic causalities run from output and inflation to money creation. Hence, money growth does not explain inflation. Besides, the result does not require a sophisticated microfoundation of money demand but simply emerges from the transmission process.
Keywords: E44; E51; 330; quantity equation; endogenous money; New Keynesian Macroeconomics; inflation targeting; money demand